Screening of Salmonella enterica Serovars, Typhi, Typhimurium, and Enteritidis in Raw Milk and Dairy Products in South-Khorasan, Iran: Conventional versus Molecular Method - Zeinali, Tayebeh; Naseri, Kobra; Zandi, Nasrin; Khosravi, Matin (Current Nutrition & Food Science, 2020)
Background and Objective: Food-borne Salmonellosis has been reported as the second most common bacterial infection. Salmonella enterica subsp. enterica serotype enteritidis (S. Enteritidis) and S. enterica subsp. enterica serotype typhimurium (S. Typhimurium) are the most common serotypes worldwide as salmonellosis agents. Salmonella yyphi is the causative agent of typhoid fever worldwide. The purpose of the present study was to determine the contamination rate of raw milk and dairy products to Salmonella typhi, S. typhimurium and S. Enteritidis in South-Khorasan, Iran. It is very important in food safety risk assessment and human health. Methods: A total of 260 raw milk and 181 dairy products were obtained from South-Khorasan, Iran. Dairy samples were pre-enriched in buffered peptone water and enriched in Rappaport Vassiliadis (RV). Raw milk was enriched in RV. Plating of the enriched samples was carried out on Xylose Lysine Desoxycholate (XLD) agar and Brilliant Green agar (BGA). All of the enriched samples were also tested by M-PCR for detection of S. typhi, S. typhimurium and S. Enteritidis. Results: Among the 441 tested samples only 4 samples were contaminated with Salmonella spp. in culture method. PCR assay, didn’t find any positive sample regarding Salmonella spp. In chi-square test, the difference of two methods of isolation was significant (P< 0.05). Conclusion: In conclusion, the results of the present study showed a good hygienic state of raw milk and dairy products. Enrichment based PCR assay is more economical than time-consuming culture method for Salmonella detection.
Keywords: food safety